The Effect of Job Demands on Psychological Well-Being through Job Stress: Evidence from the Beauty Industry - Kartika Rahayu; Benny Bernadus (International Journal of Marketing & Human Resource Research, 2026)
The beauty industry is characterized by rapid innovation cycles, intensive promotional activities, and high competitive pressure, which place substantial demands on employees, particularly those working in promotion-related functions. This study aims to examine the effect of job demands on employees’ psychological well-being, with job stress positioned as a mediating variable. Using a quantitative, cross-sectional design, data were collected from promotion employees of a beauty company in Bandung, Indonesia. The analysis employed multiple regression and mediation testing to assess the direct and indirect relationships among job demands, job stress, and psychological well-being. The findings indicate that job demands have a significant positive effect on job stress, while job stress has a significant negative effect on psychological well-being. In addition, job demands are found to negatively affect psychological well-being both directly and indirectly through job stress, confirming the mediating role of job stress. These results suggest that high promotional intensity and workload in the beauty industry can undermine employees’ psychological functioning when not accompanied by adequate coping and organizational support mechanisms. This study contributes to the job demands–well-being literature by providing industry-specific evidence from the beauty sector and highlights the importance of managing job stress as a strategic human resource priority to sustain employee well-being in highly competitive environments